The study on the impact of sex on the structure of gut microbiota of bamboo rats in China - Gan, Yang; Wu, Yan-jun; Dong, Yuan-qiu; Li, Qian; Wu, Shu-guang; Jin, Yuan-qing; Lu, Tao-feng (Frontiers in Microbiology, 2023)
Bamboo rats are rodents that eat bamboo, and their robust capacity for bamboo digestion is directly correlated with their gut flora. Chinese bamboo rat (Rhizomys sinensis) rat is a common bamboo rat in Chinese central and southern regions. In this study, the gut microbiome of bamboo rats from different genders was compared based on the 16S rRNA amplicon sequencing, and cellulasesproducing bacteria were isolated and identified from the feces of bamboo rats. The results show that a total of 3,833 OTUs were classified. The total microbial diversity detected in the Female and Male group consisted of 3049 OTUs and 3452 OTUs, respectively. For the differences in microbial diversity, the Shannon index has significant differences between the two groups (P<0.05), and the two groups are different even though they are all captive in the same feeding conditions. Among the phylum level, Firmicutes, Bacteroidota and Proteobacteria were the main enrichment microbial community. Among the genus level, the microbial community was dominated by Lachnospiraceae, Lactobacillus, Bacteroides and Prevotella, but there is a significant difference between the two groups of bamboo rats. For the difference in bacteria genus between the two groups, the 90 bacteria genus in the female group was significantly higher than the male group at the genus level. Among them, the Bacteroides, Colidextribacter and Oscillibacter were significantly higher genera, and the genus of Lachnoclostridium, Oscillibacter and Papillibacter had the biggest FC value among the male and female bamboo rats. For KEGG function annotation and different pathways analysis, Membrane Transport, Carbohydrate Metabolism and Amino Acid Metabolism are the most enriched metabolic pathways in the two groups, and multiple sugar transport system permease protein (K02025 and K02026), RNA polymerase sigma-70 factor (K03088) and ATP-binding cassette (K06147) were the three different KEGG pathways (P < 0.05). Two cellulose degradation bacteria strains, Bacillus subtilis and Enterococcus faecalis, were isolated and characterized from the feces of bamboo rats for the isolation and screening of cellulose degradation bacteria.